2015 Food policy timeline: Issues, actions and events - International Food Policy Research Institute (International Food Policy Research Institute, 2016)
The Global Food Policy Report is IFPRI’s flagship publication. This year’s annual report examines major food policy issues, global and regional developments, and commitments made in 2015, and presents data on key food policy indicators. The report also proposes key policy options for 2016 and beyond to achieve the Sustainable Development Goals. In 2015, the global community made major commitments on sustainable development and climate change. The global food system lies at the heart of these commitments—and we will only be able to meet the new goals if we work to transform our food system to be more inclusive, climate-smart, sustainable, efficient, nutrition- and health-driven, and business-friendly.